encryption - Prove the decryption by counter mode is correct -


as review question have prove decryption process of counter mode correct. how prove it? no other information given.

encryption: cj = e(k, counter + j -1) ⊕ pj  decryption: pj = e(k, counter + j -1) ⊕ cj 

pj = e(k, counter + j -1) ⊕ cj 

replace cj = e(k, counter + j -1) ⊕ pj

cj = e(k, counter + j -1) ⊕ e(k, counter + j -1) ⊕ pj  

since x⊕x=0 (the encrypted counter xored itself) , 0⊕x=x

pj = 0 ⊕ pj  pj = pj 

qed


Comments

Popular posts from this blog

get url and add instance to a model with prefilled foreign key :django admin -

css - Make div keyboard-scrollable in jQuery Mobile? -

ruby on rails - Seeing duplicate requests handled with Unicorn -